Eradicating Corporal Punishment in Pakistan: Upholding Children's Rights and Promoting Healthy Development - Masood Ali Shaikh,; Syed Muhammad Mubeen, (Journal of the Pakistan Medical Association, 2025)
The physical form of disciplining children is the mostcommon form of violence globally in this demographic.1“The right of child to protection from corporal punishmentand other cruel or degrading forms of punishment” wasdeveloped by the United Nations Committee on the Rightsof the Child in its General Comment 8 in 2006. It went onto provide a clear definition of physical/corporalpunishment as “any punishment in which physical force isused and intended to cause some degree of pain ordiscomfort, however light”.2 It provided examples of suchpunishment as: ‘smacking’, ‘slapping’, ‘spanking’, and manyother forms of more severe physical violence; and deemedit degrading for the child. It also defined “Child” as “everyhuman being below the age of eighteen years unless underthe law applicable to the child, the majority is attainedearlier. ”.By“ the majority is attained earlier” implies the legalage at which a person is considered an adult according totheir country's laws. Continue...